Radiographic outcomes following femoroacetabular impingement correction with open surgical management: a systematic review - Martin, R. Kyle (Curr Rev Musculoskelet Med, 2016)
Femoroacetabular impingement (FAI) is a common cause of hip pain, and open surgical approaches remain an important treatment option for FAI. This systematic review of the literature sought to determine what post-operative radiographic outcomes have been reported following open surgical correction of FAI. After screening and full-text review, 18 studies involving 1192 hips in 1084 patients were included for analysis. In total, 24 radiological outcomes were reported. CAM-type FAI was most frequently assessed using the alpha angle (61.1 %) and head-neck offset/head-neck offset ratio (33.3 %). Lateral center edge angle (27.8 %) and the acetabular index (22.2 %) were the most commonly reported outcomes for pincer-type FAI. The results of this review suggest that reporting of post-operative radiographic outcomes is variable, that no single radiographic parameter is optimal, and that the clinician must use a combination of reproducible measurements, together with their clinical examination, to confirm adequate restoration of normal hip morphology. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12178-016-9365-4) contains supplementary material, which is available to authorized users.